PENGARUH KOMPOSISI MASSA KITOSAN TERHADAP POROSITAS MEMBRAN NANOKITOSAN-GELATIN - , FITRI RAHMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chitosan contributes in the drug delivery system which has biological properties including non-toxic, biocompatibility, and biodegradation. Chitosan is developed in nanoparticle size because it has the ideal properties of polymers for nanoparticles with the aim to ensure more secure and efficient of drug delivery. Chitosan can be mixed with gelatine into membranes. The addition of gelatine can improve chemical, physical, and biological properties of chitosan membrane. The porosity of membranes is considered influential on biodegradation activity and ability to release molecules in membranes. The aim of this study is to determine the effect of chitosan mass composition to the nanoparticle chitosan-gelatine membranes porosity. Five nanoparticle chitosan-gelatine membrane samples were used in each study group with different mass of chitosan, 0.6 g, 0.8 g, and 1 g each. Nanoparticle chitosan-gelatine membranes were prepared by mixing nanoparticle chitosan solution and gelatine. The porosity of nanoparticle chitosan-gelatine membranes were calculated using the formula of porosity determination that has been used in previous study. Data obtained was in the form of porosity percentage that were analyzed using one-way ANOVA test to compare the porosity between the 3 study groups. One-way ANOVA test result showed a significant influence between mass composition of chitosan to the porosity of nanoparticle chitosan-gelatine membranes. LSD test result showed that the porosity of nanoparticle-chitosangelatine membranes had significant differences between chitosan mass 0.6 g to 0.8 g and 0.6 g to 1 g. It was concluded that the chitosan mass composition affects the porosity of nanoparticle chitosan-gelatine membranes. Key words : chitosan, gelatine, nanoparticle chitosan-gelatine membrane, porosity